Participative Leadership Style of School Heads: Implications for an Effective Academic Mentorship Program - Villafane, Raymond (Journal of Interdisciplinary Perspectives, 2025)
This study explores how school heads in the Schools Division of Bulacan apply participative leadership in their daily work and how it influences decision-making and school improvement. While leadership is crucial to educational success, there is limited research on how participative leadership is practiced in this setting. There is also a lack of mentorship programs designed to support school heads in strengthening this leadership approach. This study aims to fill these gaps by examining the leadership practices of school heads and developing a mentorship program to enhance their effectiveness. A mixed- method, explanatory-sequential approach was used, combining surveys and interviews. The study included 81 secondary school heads for quantitative data and 15 informants for qualitative insights. Results showed that school heads consistently demonstrated participative leadership, with most practices rated to a "Very Great Extent." However, challenges such as resistance to change, lack of cooperation, and time constraints were identified. Other difficulties included personal issues, student disengagement, limited parental involvement, and weak community connections. Overcoming these obstacles requires strong community support, clear communication, and active stakeholder engagement. Best practices for participative leadership include involving stakeholders, being resilient, and maintaining effective communication. The study highlights improved collaboration, increased teacher engagement, and a better work environment. Key support strategies include teamwork, recognition, and training programs. Based on these findings, an academic mentorship program was designed to help school heads develop sustainable and effective leadership practices, ensuring long-term improvement in school leadership.